Apo Reef Marine Life Observatory - Flores, Melwyn Ruth V.
Apo Reef Natural Park is the world's second largest contiguous coral reef system and an enormous undersea food factory. It forms the apex of the Coral Triangle which is the Global Center of Marine Biodiversity. Despite its importance, it is currently undervalued due to mismanagement and lack of funding. This can wipe out the reefs in the Philippines and cause economic crisis. Hence, it implies the necessity of having a facility which allows optimum acquisition of knowledge and strengthen community participation of Filipinos on marine conservation. Apo Reef Marine Life Observatory is an integrated recreational and environmental project which focuses on biological conservation and awareness through experiential learning. A floating structure which aims to attract international expertise, local support, and external sources of income. As well as ensure proper management of the coast and raise public awareness. At the end of the line, it will not only be beneficial to the science field but it will also make an impact in the ecosystem even beyond the Philippine boundary. Because saving the coral reefs is more than just biodiversity conservation, it also affects the food supply and livelihood of millions of people.